English Teacher Identity Crisis after Fruitless Virtual Teaching Practices During Covid-19 Outbreak in Underprivileged Institution - Wiramarta Kadek; Ni Putu Dian Utami Dewi (Mimbar Ilmu, 2022)
Education institutions are under proliferating challenges to deliver successful virtual learning in an increasingly digitized and globalized environment and especially during Covid-19 outbreak. This even become harder in academically challenging circumstance. This might put their identity as a teacher in hard situation. The aim of this research is to analyses English teacher attitudes and perception after having unsuccessful teaching practices from professional identity lens. An interpretative phenomenological analysis by utilizing dialogic interview will be employed to 4 higher education English teacher in underprivileged and newly established university to capture the intended data. After that, the data regarding teacher identity will be displayed and extensively analysed to unfold some individual phenomenon while implementing virtual classroom to teach English. This study found that our participants have evidently grown professionally during the Covid-19 epidemic time frame. Several teachers have developed some strategies to actually engage students in the virtual classroom and gained more awareness of technological issues in learning. In fact, this experience was viewed as enhancing their teacher identity. This study is expected to offer a glimpse of teacher individual situation and some insight on the effort in maintaining personal teachers’ identity during virtual learning process.